We start with a commutative operation, addition, and iterate it recursively to arrive at the operation, multiplication as repeated addition, and find that it remains commutative. One might assume that a statement such as "iterated commutative operations are again commutative". In which case one would expect exponentiation which is also an iteration of a commutative operation, to itself be commutative. But exponentiation is not commutative, so the expected statement does not hold. Why not?
Well let's look at the proof of the commutativity of multiplication from the axioms of Peano arithmetic.
Denote the successor of $n$ as $s(n).$ Multiplication is defined recursively via $s(m)\cdot n = m\cdot n + n$ with a base case of $0\cdot n=0.$
We wish to show that $m\cdot n = n\cdot m$ for all $m,n\in\mathbb{N}.$ We proceed by induction on $m$ nested inside an induction on $n$. Let $S$ be the set of naturals that commute with everything in $\mathbb{N}$. Clearly $0\in S$. Suppose $n\in S$. Let $T$ be the set of all naturals that commute with $S(n)$. Clearly $0\in T$. Suppose $m\in T.$ Then we have
$$
s(m)\cdot s(n) = m\cdot s(n) + s(n)\qquad\text{(def of mult)}\\
= s(n)\cdot m + s(n)\qquad\text{(ind hyp 2)}\\
= (n\cdot m + m) + s(n)\qquad\text{(def of mult)}\\
= n\cdot m + (m + s(n))\qquad\text{(add assoc)}\\
= n\cdot m + s(m + n)\qquad\text{(def of add)}\\
= n\cdot m + s(n + m)\qquad\text{(add comm)}\\
= n\cdot m + (n + s(m))\qquad\text{(def of add)}\\
= (n\cdot m + n) + s(m)\qquad\text{(add assoc)}\\
= (m\cdot n + n) + s(m)\qquad\text{(ind hyp 1)}\\
= s(m)\cdot n + s(m)\qquad\text{(def of mult)}\\
= n\cdot s(m) + s(m)\qquad\text{(ind hyp 1)}\\
= s(n)\cdot s(m)\qquad\text{(def of mult)}.
$$
So $s(m)\in T$ and therefore $T=\mathbb{N}.$ Therefore $s(n)\in S$, and so $S=\mathbb{N}$.
Now let's repeat the proof, line for line, but changing mutatis mutandi the addition to multiplication and the multiplication to exponentiation, to see where it fails.
Define exponentiation recursively as $m^{s(n)} = m^n\cdot m,$ with base case $m^0 = 1.$
$$
s(n)^{s(m)} = s(n)^m \cdot s(n)\\
= m^{s(n)} \cdot s(n)\\
= (m^n \cdot m) \cdot s(n)\\
= m^n \cdot (m \cdot s(n))\\
= m^n \cdot \color{red}{s(m \cdot n)}\\
= m^n \cdot s(n \cdot m)\\
= m^n \cdot \color{red}{(n \cdot s(m))}\\
= (m^n \cdot n) \cdot s(m)\\
= (n^m \cdot n) \cdot s(m)\\
=n^{s(m)} \cdot s(m)\\
= s(m)^n \cdot s(m)\\
= s(m)^{s(n)}.
$$
The two steps in red are the invalid steps (besides also the base case fails), which assume that the successor of a product is a product with the successor of one of the factors, which fails: $\color{red}{s(m\cdot n) \neq m\cdot s(n)}$. So this is the reason that the formal proof of commutativity of multiplication fails to carry over to a proof of commutativity of exponentiation. This is the difference between addition and multiplication: the successor operation commutes with addition but not multiplication. $$(m+1)+n=(m+n)+1,$$ but $$(m+1)\cdot n\neq (m\cdot n)+1$$.
Multiplication distributes over addition and the successor operation, rather than commuting with it.
To say it another way, the question shouldn't be "why isn't exponentiation commutative?". The better question is "why is multiplication commutative?" Addition is commutative because successor is associative, and multiplication is commutative because, recursively viewed, it's just addition, and addition commutes with successor. For no other operations, certainly no higher iterates, should we expect this to be true.
Note that this is essentially the same answer as Lieven gave: if we use a multiplicative recursion instead of additive, then parallels between iterated of addition and multiplication do exist. But I wanted to see an answer that pinpoints the precise step where the proof breaks down, hence my submission.